Crystal structure of the pyridoxal-5′-phosphate-dependent serine dehydratase from human liver - Sun, Lei (Cold Spring Harbor Laboratory Press, 2005)
L-serine dehydratase (SDH), a member of the β-family of pyridoxal phosphate-dependent (PLP) enzymes, catalyzes the deamination of L-serine and L-threonine to yield pyruvate or 2-oxobutyrate. The crystal structure of L-serine dehydratase from human liver (hSDH) has been solved at 2.5 Å-resolution by molecular replacement. The structure is a homodimer and reveals a fold typical for β-family PLP-dependent enzymes. Each monomer serves as an active unit and is subdivided into two distinct domains: a small domain and a PLP-binding domain that covalently anchors the cofactor. Both domains show the typical open α/β architecture of PLP enzymes. Comparison with the rSDH-(PLP-OMS) holo-enzyme reveals a large structural difference in active sites caused by the artifical O-methylserine. Furthermore, the activity of hSDH-PLP was assayed and it proved to show catalytic activity. That suggests that the structure of hSDH-PLP is the first structure of the active natural holo-SDH.